Association of prospective lower extremity musculoskeletal injury and musculoskeletal, balance, and physiological characteristics in Special Operations Forces. (November 2017) - Keenan, Karen A.; Wohleber, Meleesa F.; Perlsweig, Katherine A.; Baldwin, Thomas M.; Caviston, Michael; Lovalekar, Mita; Connaboy, Christopher; Nindl, Bradley C.; Beals, Kim
Abstract: Objectives: Previous research has examined lower extremity (LE) musculoskeletal injury (MSI) patterns and risk factors in Special Operations Forces (SOF) trainees, conventional military personnel, and athletes; however, it is unclear if SOF have the same patterns/risk factors. This study aimed to determine the association of musculoskeletal, balance, and physiological characteristics with LE MSI in SOF. Design: Cohort study. Methods: A total of 726 Air Force (N = 140), Navy Sea, Air, and Land (N = 301), and Special Warfare Combatant Crewmen (N = 285) SOF (age = 25.72 ± 4.77 years, height = 178.34 ± 6.63 cm, weight = 84.28 ± 9.03 kg) participated in laboratory testing, including: LE muscular strength and flexibility; balance; body composition; anaerobic power/capacity; and aerobic capacity. Medical charts were reviewed for LE MSI 365 days following laboratory testing. Participants were assigned by injury status and laboratory data stratified by tertile. Chi-square statistics were calculated to determine the frequency of LE MSI across tertiles for each characteristic. Results: There was a significant association between LE MSI and: ankle inversion strength (weaker side: Χ (2) = 17.703; stronger side: Χ (2) = 18.911; p ≤ 0.001); ankle eversion/inversion strength ratio (lower side: Χ (2) = 13.456; higher side: Χ (2) = 16.885; p ≤ 0.001); hamstring flexibility (less flexible: Χ (2) = 19.930; more flexible Χ (2) = 15.185; p ≤ 0.001); gastrocnemius-soleus flexibility (less flexible: Χ (2) = 7.889, p = 0.019); dynamic balance asymmetry ( Χ (2) = 7.444, p = 0.024); Vestibular and Preference ratios ( Χ (2) = 9.124, p  = 0.010 and Χ (2) = 6.572, p = 0.037, respectively); and aerobic capacity ( Χ (2) = 13.935, p = 0.001). Conclusions: Characteristics associated with LE MSI are unique in SOF. Human performance program initiatives should include efforts to optimize ankle strength and flexibility, maintain moderate hamstring flexibility, expand dynamic balance strategies, and maximize aerobic capacity to reduce LE MSI risk.